Comprehensive assessments of pulmonary circulation in children with pulmonary hypertension associated with congenital heart disease - Muneuchi, Jun; Ezaki, Hiroki; Sugitani, Yuichiro; Watanabe, Mamie (Frontiers in Pediatrics, 2022)
Pulmonary hypertension associated with congenital heart disease (CHD-PH) encompasses different conditions confounded by the left-to-right shunt, left heart obstruction, ventricular dysfunction, hypoxia due to airway obstruction, dysplasia/hypoplasia of the pulmonary vasculature, pulmonary vascular obstructive disease, and genetic variations of vasoactive mediators. Pulmonary input impedance consists of the pulmonary vascular resistance (Rp) and capacitance (Cp). Rp is calculated as the transpulmonary pressure divided by the pulmonary cardiac output, whereas Cp is calculated as the pulmonary stroke volume divided by the pulmonary arterial pulse pressure. The plots of Rp and Cp demonstrate a unique hyperbolic relationship, namely the resistor-capacitor coupling curve, which represents the pulmonary vascular condition. The product of Rp and Cp is the exponential pressure decay, which refers to the time constant. Alterations in Cp are more considerable in CHD patients at an early stage of developing pulmonary hypertension or with excessive pulmonary blood flow due to a left-to-right shunt. The importance of Cp has gained attention because recent reports have shown that low Cp potentially reflects poor prognosis in patients with CHD-PH, as well as idiopathic pulmonary hypertension. It is also known that Cp levels decreases in the specific populations, such as preterm infants and trisomy 21. Therefore, both Rp and Cp should be individually evaluated in the management of children with CHD-PH who have different disease conditions.